Pengaruh Pengairan Separuh Daerah Akar terhadap Efisiensi Penggunaan Air dan Produksi Kedelai (Glycine max L.) pada Musim Kemarau - Andi Bahrun (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
A new method of irrigation was designed for increasing water use efficiency (WUE) and yield of field grown soybeanduring dry season. This experiment consisted of four treatments , namely (1) the whole root zone system was irrigated with4 L m-2; (2) the partial root zone system was irrigated with 4 L m-2; (3) the partial root zone system was irrigated with 3 Lm-2; and (4) the partial root zone system was irrigated with 2 L m-2. Partial root zone irrigation treatments were done bydaily watering one side between two plants row while the other side was allowed to dry and irrigation was shifted to the dryside while the wet side was allowed to dry every 7 days irrigation interval, respectively. The experiment was designed as arandomized complete block design with four replications and a 2.6 m x 2.4 m plot size. The results showed that the partialroot zone irrigation treatment maintained growth, biomass, nodule, relative leaf water content, relative leaf chlorophyllcontent, leaf nitrogen content and yield at the level of fully irrigated treatment and increased leaf ABA content and water useefficiency, but the effect depended on volume of water applied. Partial root zone irrigation with 2 L m-2 and 3 L m-2 irrigationdecreased yield by 2.97% and 16.91%, respectively, however, those treatments increased water use efficiency by 29.97% and23.63%, respectively, compared to those with fully irrigated plots.Keywords: ABA, irrigation, soybean, root zone, water use efficiency